Resistência a antimicrobianos em Staphylococcus aureus - Faria, Rafael César Bolleli (2008)
Multiple antibiotic resistant Staphylococcus aureus represent a big problem in the control of hospital infections. Resistance pattern of isolated S. aureus presented in central vascular catheter of patients interned in the Intensive Therapy Center of the School Hospital of the Universidade Federal do Triângulo Mineiro was evaluated by antimicrobial tests, in which it was possible to detect high level of resistance to penicillin (94.7%) and ampicillin (86.8%), only considering the samples that presented resistance, beyond one strain that presented resistance to vancomycin. The oxacillin resistance evaluation was confirmed by PCR with the presence of the gene mecA. The association of the results obtained in the phenotypic test with the presence of the gene mecA, considered the reference method, was confirmed through the Table of Contingency and the Test of Χ2 with Yates correction. In 49 isolates evaluated, 23 were resistant to oxacillin, being possible to detect the mecA gene in 21 samples. The test of molecular screening by RAPD allowed the separation of the phenotypic groups in two different grouping patterns, the ones that presented resistance to antimicrobials and the sensible ones, with a dissimilarity of 73,3%. There is a higher genetic similarity between groups that present the same type of resistance, thus confirming the phenotypic analyses. Molecular markers for detection of resistance to oxacillin, like the gene mecA, were more sensitive than the phenotypic markers.